PENGABDIAN KEPADA MASYARAKAT DENGAN PELATIHAN MENULIS PUISI MENGGUNAKAN MEDIA GAMBAR PADA SISWA KELAS 5 SD AMBARITA, SAMOSIR - Andani, Annisah Fitri (CV. Alfa Pustaka, 2024)
This community service activity aims to improve the ability to write poetry for 5th grade students of SD Ambarita, Samosir, through a picture media-based approach. The methods used include providing a basic understanding of poetry, image observation, poetry writing guidance, as well as presentations and discussions. From the training involving 30 students, the results of the evaluation showed that 85% of the students successfully understood the elements of poetry, 70% of the students were able to produce poems with good structure, and 90% of the students showed an increased interest in writing poetry. This activity also succeeded in creating an interactive and fun learning atmosphere. This training has a positive impact on students' creativity and literacy skills, so it is recommended to continue with more varied themes and approaches.